A comparative morphologic analysis of benchmark sets of project networks - Tavares, Luís Valadares (2011)
The performance of methods to manage projects depends heavily on the features of their project networks. This is particularly true for methods devoted to project scheduling, risk analysis and resources allocation. Therefore, a long line of research has been developed to generate benchmark sets of project networks and several sets have been proposed in the literature. Unfortunately, no comparative analyses of their features were published and hence serious doubts about the comparability of results using different benchmark sets can be raised. In this paper, a multi-dimensional taxonomy for the morphology of project networks is used and four benchmark sets are evaluated: Patterson collection of problems (Patterson JH. A comparison of exact approaches for solving the multiple constrained resource, project scheduling problem. Management Science 1984;30:854–867) and the sets produced by the generators due to Agrawal et al. Agrawal MK, Elmaghraby SE, Herroelen WS. DAGEN a generator of testsets for project activity nets. European Journal of Operational Research 1996;90:376–382, Kolisch et al. Kolisch R, Sprecher A, Drexl A. Characterization and generation of a general class of resource — constrained project scheduling problems. Management Science 1995;41:1693–1703, Tavares Tavares LV. Advanced models in project management. Kluwer, 1999 and Tavares et al. Tavares LV, Antunes Ferreira JA, Coelho JS. The risk of delay of a project in terms of the morphology of its network. European Journal of Operational Research 1999;119:510–537. Original results about the lack of representativeness of these sets are obtained showing that misleading conclusions can be deduced. The last set is, by far, that one covering most extensively the morphologic space of instances which could be foreseen because the generation of networks is carried out in terms of an wider range of parameters. This conclusion is quite useful for project managers willing to assess alternative methods to solve their problems based on project networks.